BUDIDAYA JAMUR PERUSAK KAYU V. BUDIDAYA PLEUROTUS FLABELLATUS PADA ENAM JENIS KAYU - Sihati Suprapti; Ginuk Sumami (Jurnal Penelitian Hasil Hutan, 1988)
Pink oyster   mushroom (Pleurotus  flabellatus)  was  cultivated   on  logs of  six  wood  species,   i.e.  hamerang  (Ficus grossularoides Burn.f.),  jeungjing   (Albizia   falcataria   (L.)  Fosb.),  jirak  (Symplocos fasciculata Zoll.), kihuut   (Vernonia arborea  Ham.),   manii  (Maesopsis eminii  Engl.)  and seuseureuhan   (Piper aduncum L.).  The  logs were  kept  slanted  on an angle of  ± 60°  with  bamboo  supports   in a house  at Gunung Bunder  Forest  Complex, Bogor,  The mature  mushroom   were harvested  daily.The logs start producing  fungus  two  months  after inoculation. The average yield per log during one year observation was 581.8 g (hamerang,) 178.83g (manii),  69.23g (jeungjing), 25.47  g (kihuut), 19.44g  (jirak), and 18.47 g (seuseureuhan).The average yield  per month  per  m3 of log was obtained  from  hamerang  7.52 kg,  man ii 1. 72 kg, jeungjing  0.58 6 kg, seuseureuhan   0.44  kg.  jirak  0.321 kg and kihuut   0.244  kg.The total yield  in one year observation  was obtained  from  hamerang  (90.20 kg),  manii (20.67 kg), jeungjing  (7.03 kg),  seuseureuhan (5.3kg), jirak  (3.85kg)  and kihuut (2.93  kg) per  m3  of log.